INOVASI BAHAN AJAR PRAGMATIK BERBASIS KEARIFAN LOKAL DENGAN METODE PERMAINAN BAHASA (LANGUAGE GAME) DI SEKOLAH DASAR - Eneng Nidha Widiarahmi; Rina Heryani (Jurnal Pendidikan Dasar, 2025)
Contextual communication skills are essential for elementary school students; however, Indonesian language learning still emphasizes structural and grammatical aspects, resulting in limited pragmatic competence. In addition, teaching materials have not optimally integrated local wisdom as a learning context. This study aims to develop and examine the effectiveness of pragmatic teaching materials based on local wisdom using the language game method in elementary schools. The research employed a Design-Based Research (DBR) approach consisting of problem analysis, prototype design, implementation and revision, and reflection. The participants were teachers and fourth-grade students at a public elementary school in Bandung. Data were collected through interviews, classroom observations, expert validation, and pretest–posttest assessments of pragmatic skills. The results indicate that the developed teaching materials achieved very high validity in terms of readability, content relevance, and integration of local cultural values. The limited trial revealed a significant improvement in students’ pragmatic competence, as the average score increased from 74.00 on the pretest to 88.74 on the posttest. In conclusion, pragmatic teaching materials based on local wisdom and implemented through language games are effective in enhancing students’ pragmatic language skills, politeness, and active participation in elementary Indonesian language learning.